Adequacy of electrical conductivity test for lentil seeds - Silva, Edvan Costa da; Menechini, Wagner; Galvão, Carolina dos Santos; Oliveira, Luís Augusto Batista de; Ferreira, Natália Cássia de Faria; Silva, Luciana Sabini da (Scientia Agraria Paranaensis, 2020)
The electrical conductivity test stands out among the existing physiological quality tests due to its simplicity of execution, repeatability, speed, easy interpretation of results, and low cost. This study aimed to establish a methodology for the test of electric conductivity in lentil seeds (Lens culinaris Medik), involving the seeds’ number of seeds and soaking time. The experiment was conducted at the Multidisciplinary Laboratory of the State University of Goiás, Campus Ipameri, in 2018. Lentil Silvina seeds were used, stored in the seed laboratory of the same institution. The experimental design used was completely randomized, in a 4x5 factorial scheme, with four seed lots (25, 50, 75, and 100 seeds) and five soaking times (3, 6, 9, 12, and 15 hours) at 25 ºC, with four replications. The initial seed quality was characterized (water content, first counting of germination, percentage of germination, accelerated aging and 1000-seed weight). For the electrical conductivity test, four repetitions of 25, 50, 75, and 100 seeds each were used, weighed on a digital scale with an accuracy of 0.001 g and placed in plastic cups, with a capacity of 200 mL, containing 75 mL of distilled water. Then, the plastic cups remained in a BOD chamber, adjusted at 25 °C and the measuring was performed after 3, 6, 9, 12, and 15 hours of soaking in a conductivity meter (DIGIMED DM 31), the results being expressed in μS cm-1 g-1. There was a significant interaction when evaluating the number of seeds per repetition and the soaking time. The use of replicates with 50 seeds subjected to 12 h of soaking shows the best results for the lentil seeds’ electrical conductivity test.